PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SIFAT-SIFAT PERIODIK UNSUR KELAS X DI SMAN 1 SURANENGGALA - Andri Supriadi; Eny Winaryati; Dian Wulandari (Journal of Lesson Study in Teacher Education, 2024)
This research is classroom action research which aims to improve the quality of learning and student learning outcomes. The objects of this research were students in class The method in this research is a qualitative descriptive method. Classroom action research design with three steps, namely Planning, Implementation, and Reflection. The indicator of success in this research is the achievement of student competency from cognitive learning outcomes which reached 92% completion with a KKM = 75. In carrying out the assessment in this activity, learning technology media through Quizizz is used to facilitate data processing to make it more efficient and effective. Through this learning, it is hoped that students will be able to grow their imagination and develop their thinking power to achieve the 4 character skills of the 21st century, such as: Critical Thinking and Problem Solving, Communication, Collaboration, and Creativity and Innovation.